(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aims to uncover the difficulties faced by students in the marketing field as they promote their products and services. Student entrepreneurs encounter various challenges, including limited resources, a lack of marketing knowledge or experience, and the difficulty of juggling their academic commitments with their business activities. For those attempting to grow their businesses, meeting assignment deadlines and studying for exams can be especially challenging. A descriptive research methodology was employed to systematically examine the challenges faced by student entrepreneurs in promoting their businesses. Data were collected using a survey questionnaire, enabling the researchers to gather quantitative and qualitative insights directly from the participants. Purposive sampling was utilized to select respondents who are college students actively engaged in business promotion, ensuring that the sample is directly relevant to the research objectives. This approach facilitated an in-depth understanding of how these students address marketing challenges within their entrepreneurial endeavors. The study identifies key challenges faced by student entrepreneurs in promoting their products and services, highlighting areas such as time management, professionalism, and product development. Addressing these challenges with targeted strategies can enhance their marketing effectiveness and overall business success. This study aims to understand the challenges faced by student entrepreneurs and identify effective solutions to address them. Researchers emphasize the importance of proactive engagement, suggesting that students should anticipate potential problems and develop strategies to mitigate risks. Implementing flexible scheduling, participating in mentorship programs, and utilizing time management tools are recommended to help students balance academic and business responsibilities effectively. Additionally, fostering professional growth through continuous learning and networking is crucial for their entrepreneurial success.​